Immature instars of three species of Rhodnius Stål, 1859 (Hemiptera, Reduviidae, Triatominae): morphology, morphometry, and taxonomic implications - Lázari Cacini, Gustavo [UNESP]; de Oliveira, Jader; Belintani, Tiago; dos Santos Souza, Éder; Olaia, Nicoly [UNESP]; Pinto, Mara Cristina [UNESP]; da Rosa, João Aristeu [UNESP] (Springer Nature, 2022)
Background: Among the 18 genera of the Triatominae subfamily, three stand out for their diversity and epidemiological importance: Triatoma, Panstrongylus, and Rhodnius. Rhodnius includes 21 species that can transmit Trypanosoma cruzi (the etiological agent of Chagas disease, also known as American trypanosomiasis) and Trypanosoma rangeli. The Rhodnius prolixus complex comprises seven species, including Rhodnius marabaensis, Rhodnius prolixus, and Rhodnius robustus, which occur in the northern region of Brazil. Since both adults and immatures can carry T. cruzi, in this study the five nymphal instars of the three species mentioned were dorsally characterized. Methods: Using microscopy, morphometrics, and geometric morphometrics, the present work measures and describes the morphological characters of the five nymphal instars of R. marabaensis, R. prolixus, and R. robustus. Results: The study enabled the characterization of all five nymphal instars, as well as the distinction between the three species in each of their instars. Conclusions: The morphological, morphometrics of the head, thorax, and abdomen and geometric morphometrics studies of the head enabled the specific distinction of these three species in all five instars. Graphical Abstract: [Figure not available: see fulltext.].S
Keywords: Chagas disease; Rhodniini; Rhodnius; Triatomines; Vector